2001
DOI: 10.1143/jjap.40.l195
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of AlxGa1-xN/GaN Heterostructure –Compositional and Impurity Dependence–

Abstract: Grown-in stress and subsequent fracture in Al x Ga1-x N/GaN heterostructures with or without impurity doping were studied in situ. It was found that the critical thickness of Al x Ga1-x N depends not only on its composition but also on the concentration of impurities such as Si or Mg. Increase in tensile stress during growth at a constant AlN molar fraction can be explained by the increase in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 14 publications
0
18
2
Order By: Relevance
“…As for the stress, σ zzAlGaN is approximately 1.7 times larger than σ xxAlGaN at each x. Compared with the reported values for c-plane AlGaN on GaN [16], σ xxAlGaN values in this study are nearly identical at all x values, however, σ zzAlGaN is considerably larger than σ xxAlGaN . Thus, crack generation in the case of a-plane AlGaN grown on GaN, particularly in the m-axis direction, is potentially more likely than that in the case of c-plane AlGaN.…”
Section: Resultscontrasting
confidence: 47%
“…As for the stress, σ zzAlGaN is approximately 1.7 times larger than σ xxAlGaN at each x. Compared with the reported values for c-plane AlGaN on GaN [16], σ xxAlGaN values in this study are nearly identical at all x values, however, σ zzAlGaN is considerably larger than σ xxAlGaN . Thus, crack generation in the case of a-plane AlGaN grown on GaN, particularly in the m-axis direction, is potentially more likely than that in the case of c-plane AlGaN.…”
Section: Resultscontrasting
confidence: 47%
“…It has been reported that GaN on sapphire under standard conditions accumulates about 0.1-0.2 GPa/µm tensile stress (Fig. 13) [16,100] which can lead to cracking of thick layers (>5 µm) during growth [101] and can be influenced by the density of initial 3D islands at the seed layer [18] (for the physical origin of intrinsic stress see, e.g. Ref 17).…”
Section: Thick Layers and Strain Engineeringmentioning
confidence: 99%
“…They assumed this to originate in a lower impurity incorporation. Impurities like Si and Mg used for n-and p-type doping, respectively are reported to strongly enhance the tensile stress (reduce the compressive stress at RT) of GaN and AlGaN layers on sapphire [19,101]. Especially for Si doping, around 0.1 GPa/µm of additional tensile stress is induced for a doping concentration of 1 × 10 18 cm -3 .…”
Section: Thick Layers and Strain Engineeringmentioning
confidence: 99%
“…In the simplest case of linear stress-thickness dependence, the stress can be determined via the well-known Stoney equation [2]; in the case of a non-linear dependence numerical [3] or quasi-analytical solutions exist [4]. The curvature method has already been successfully applied to follow the stress evolution during metal organic vapor phase epitaxy of GaN or AlGaN on sapphire [5,6] or silicon [7]. However, to the best of our knowledge, up to now, no direct attention has been drawn to the impact of wafer bending on the substrate temperature.…”
mentioning
confidence: 99%